2010
DOI: 10.1007/978-1-60761-869-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Generation of Regulatory T Cells: Characterization and Therapeutic Evaluation in a Model of Chronic Colitis

Abstract: Naturally occurring regulatory T cells (nTregs; CD4+CD25+Foxp3+) are capable of suppressing the chronic inflammation observed in a variety of different animal models of autoimmune and chronic inflammatory diseases such as inflammatory bowel diseases, diabetes, and arthritis. A major limitation in exploring how and where nTregs exert their suppression in vivo is the relative paucity of these regulatory cells. Although several laboratories have described different methods to expand flow-purified nTregs or conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 20 publications
2
31
1
Order By: Relevance
“…This was disclosed by experiments in which unstimulated splenic CD4+CD25-cells purified from iPTH treated mice were found to express lower levels of the negative regulator of TGFβ signaling SMAD7 as compared to CD4+CD25-cells from vehicle treated mice (supplemental figure 3A). To ascertain the functional relevance of this finding, splenic CD4+CD25-cells from vehicle or iPTH treated mice were stimulated in vitro with CD3/CD28 Ab, IL-2 and TGFb at 2.5 ng/ml for 72 hours to induce their differentiation into Tregs (Karlsson, Robinson-Jackson et al, 2011). Measurements of phosphorylated SMAD2 and SMAD3 (pSMAD2 and pSMAD3) at the end of the culture period revealed higher concentrations of pSMAD2 and pSMAD3 (supplemental figure 3B) in cells from iPTH treated mice as compared to those from control mice, suggesting that conventional CD4+ T cells from iPTH treated mice have a higher sensitivity to TGFb.…”
Section: Ipth Treatment In Mice Expands the Pool Of Murine Bm Tregs Bmentioning
confidence: 99%
See 1 more Smart Citation
“…This was disclosed by experiments in which unstimulated splenic CD4+CD25-cells purified from iPTH treated mice were found to express lower levels of the negative regulator of TGFβ signaling SMAD7 as compared to CD4+CD25-cells from vehicle treated mice (supplemental figure 3A). To ascertain the functional relevance of this finding, splenic CD4+CD25-cells from vehicle or iPTH treated mice were stimulated in vitro with CD3/CD28 Ab, IL-2 and TGFb at 2.5 ng/ml for 72 hours to induce their differentiation into Tregs (Karlsson, Robinson-Jackson et al, 2011). Measurements of phosphorylated SMAD2 and SMAD3 (pSMAD2 and pSMAD3) at the end of the culture period revealed higher concentrations of pSMAD2 and pSMAD3 (supplemental figure 3B) in cells from iPTH treated mice as compared to those from control mice, suggesting that conventional CD4+ T cells from iPTH treated mice have a higher sensitivity to TGFb.…”
Section: Ipth Treatment In Mice Expands the Pool Of Murine Bm Tregs Bmentioning
confidence: 99%
“…In vitro generation of induced Tregs. The generation was carried out as described (Karlsson et al, 2011) . Briefly, purified splenic CD4+CD25-T cells from WT mice at the concentration of one million each ml completed RPMI-1640 medium were cultured in plates coated with anti-CD3 Ab (10 µg/ml) in the presence of recombinant human IL-2 (100 U/ml), TGFβ1 (20 ng/ml) and all trans retinoic acid (1 pmol/ml) for 4 days.…”
Section: Small Intestine Lamina Propria Lymphocyte (Silp) Isolation mentioning
confidence: 99%
“…It has previously been demonstrated that the Gimap5 null mutation of the BBDP strain severely compromises the function and survival of CD4 + 25 + Foxp3 + Tregs once they exit the thymus (29). To circumvent this problem, we generated induced Tregs (iTregs) from ex vivo naive CD4 + 25 2 T cells congenic for rat Ptpn22 as previously described (14,30). To examine whether differences in TCR signaling due to Ptpn22 allelic variation can affect the generation of iTregs, we stimulated cells with anti-CD28 and increasing concentrations of anti-CD3 mAbs in the presence of IL-2 and TGF-b1 for 3 d. After activation, cells were assessed for Foxp3 expression.…”
Section: The Bbdp Ptpn22 Allele Influences Treg Abundance and The Devmentioning
confidence: 99%
“…Due to their critical roles in suppressing effector T-cell activation, they have been extensively studied in the recent years. Both rodent and human studies largely depend on obtaining sufficient numbers of Tregs, which is often challenging due to the low abundance of thymic-derived (tTregs) or peripherally-induced (pTregs) Tregs (Karlsson et al, 2011; Shevach and Thornton, 2014). Therefore, alternative strategies including in-vitro differentiation and expansion of Tregs have been proposed (Chen et al, 2003; Fantini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies employing FACS sorting and/or magnetic enrichment of CD4 + T-cell populations have been published in the recent years. Currently, FACS sorting of non-Treg CD4 + T-cells is considered as the gold standard technique for obtaining pure starting populations while magnetic separation techniques have been shown to generate variable success rates which are almost always lower than sorting (Karlsson et al, 2011; Flaherty and Reynolds, 2015). However, FACS sorting requires access to advanced sorting facilities that are costly and often require scheduling in advance.…”
Section: Introductionmentioning
confidence: 99%